Polymeric microcarriers for minimally-invasive cell delivery - Duan, Chunyan; Yu, Mingjia; Hu, Changji; Xia, Hongying; Kankala, Ranjith Kumar (Frontiers in Bioengineering and Biotechnology, 2023)
Tissue engineering (TE) aims at restoring tissue defects by applying the three-dimensional (3D) biomimetic pre-formed scaffolds to restore, maintain, and enhance tissue growth. Broadly speaking, this approach has created a potential impact in anticipating organ-building, which could reduce the need for organ replacement therapy. However, the implantation of such cell-laden biomimetic constructs based on substantial open surgeries often results in severe inflammatory reactions at the incision site, leading to the generation of a harsh adverse environment where cell survival is low. To overcome such limitations, injectable microscale modularized units based on various biofabrication approaches as ideal delivery vehicles for cells and various growth factors have garnered compelling interest owing to their minimally-invasive nature, ease of packing cells, and improved cell retention efficacy. Several advancements have been made in fabricating various 3D biomimetic microscale carriers for cell delivery applications. In this review, we explicitly discuss the progress of the microscale cell carriers that potentially pushed the borders of tissue regeneration, highlighting their design, ability to deliver cells and substantial tissue growth in situ and in vivo from different viewpoints of materials chemistry and biology. Finally, we summarize the perspectives highlighting current challenges and expanding opportunities of these innovative carriers.